Paradoxes of authenticity in liminal consumption: the case of Casablanca's Rick’s café - Mamédio, Diórgenes Falcão (2024)
What makes a “fake” seemingly “authentic”? The case of Rick’s Café, known worldwide for the movie Casablanca, situates that question. Rick’s was a set constructed on a Hollywood sound stage. Another Rick’s was created materially in Casablanca decades later. Consumers are aware of this liminal condition. It is the reflexivity inherent in this awareness of performative inauthenticity that makes the case both appropriate and nuanced as an opportunity to explore paradoxes of authenticity embodied in a tourist place. The authenticity-fakery relationship is considered theoretically, not as a dualism (either-or), but as a duality (both-and). Empirically, the case is analyzed through an onsite investigation and a virtual ethnography. Four paradoxical dimensions of authenticity (liminal environment, liminal interpretation, liminal affectivity, and liminal recreation) are identified. Tourists, we submit, may experience several authenticities (i.e., objective, constructed, and existential) simultaneously and paradoxically, contributing to a reconceptualization of the tourist experience.